The influence of additional absorption on the acoustical indicators of a hall/Papildomos absorbcijos įtaka salės modelio akustiniams rodikliams - Vytautas Stauskis (Journal of Civil Engineering and Management, 1998)
The influence of the slits between the walls and the floor of the model upon the objective acoustical indicators was examined in a scaled model of a hall. The Small Hall of the Lithuanian National Philharmonic Society was selected for the investigations. The hall is of rectangular form, 13.6 m in length, 10.7 m in width and 7 m in height.